Acute Low-level Chronic Cigarette Smoke Exposure is always Harmful to Left Ventricular Function in older Rats. - Wu, Jia-Ping; Huang, Chih-Yang (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Background:Cigarette smoke (CS) exposure is associated with an increased risk of coronary artery disease. This study aim was to investigate the relationship of CS exposure in old left ventricle impaired. To explore the mechanism of cardiac remodeling of once exposure to CS exposure whether was exacerbated cardiac impaired, especially in old left ventricle. Results:Results showed LV wall and mass increased, collagen accumulation and fibrosis, and extracellular space increased in old rats in cigarette smoke exposure group (Old CSexp). From echocardiographic results, we found LV functions were apparently decreased, LV wall thickness and LV interventricular septum at systolic and diastolic diameters increased in Old CSexp group. Cardiomyocytes width was increased in old rats, but length was increased in Old CSexp rats. MMP-2 and MMP-9 proteins expression and pro-MMP2 activity reduced ECM degradation, but TIMPs were induced fibrosis increased. Calcineurin/NFAT, JNK1, p38, IL-6, TNFÎ± were increased by western blotting and immunohitochemistry in Old CSexp. Conclusions:Cigarette smoke exposure induces cardiovascular disease resulted in left ventricular hypertrophy. However, old age leads the progressive accumulation of changes of the left ventricle. Inflammatory response accelerated CS exposure induced aging-related left ventricular hypertrophy. Therefore, we suggest that acute low-level chronic cigarette smoke exposure is also harmful to left Ventricular function in old rats.